Law and International Business - PULLE, Austin Ignatius (Institutional Knowledge at Singapore Management University, 2007)
This book is the collective effort of the Law Department of the Business School of the Singapore Management University. It sets out, in an accessible yet comprehensive fashion, the basic principles of Singapore business law in the context of contract, tort, business organisations, agency, intellectual property and international business. Elements of the new economy (in particular, those pertaining to cyberspace) are also incorporated, wherever relevant. Various difficult issues and controversies are also set out in a clear and systematic fashion in order to enable the reader to bring his or her analysis to bear on the issues concerned. This book also includes the latest local as well as significant Commonwealth developments.